Trends in Substance Use Among 6th- to 10th-Grade Students From 1998 to 2010: Findings From a National Probability Study. (June 2014) - Brooks-Russell, Ashley; Farhat, Tilda; Haynie, Denise; Simons-Morton, Bruce
Of the handful of national studies tracking trends in adolescent substance use in the United States, only the Health Behavior in School-Aged Children (HBSC) study collects data from 6th through 10th graders. The purpose of this study was to examine trends from 1998 to 2010 (four time points) in the prevalence of tobacco, alcohol, and marijuana use among 6th through 10th graders. Differences in trends by grade, gender, and race/ethnicity were examined for each substance use behavior, with a primary focus on trends for sixth and seventh graders. Overall, there were significant declines in tobacco, alcohol, and marijuana use from 1998 to 2010. The declines were largest for the younger grades, which suggest promise for future declines among high school students as these cohorts age into high school.